2020
DOI: 10.1177/0033294119898120
|View full text |Cite
|
Sign up to set email alerts
|

A Matter of Perspective: An Exploratory Study of a Theory of Mind Autism Intervention for Adolescents

Abstract: Theory of Mind (ToM) is the capacity to make attributions of mental states such as thoughts, feelings, and beliefs of others. Individuals with autism spectrum disorder are often characterized by delayed or impaired Theory of Mind development and poor social skills. A positive correlation between Theory of Mind skills and social skills exists, but effective interventions that generalize these skills have proven to be a challenge in the field. Furthermore, few effective interventions exist to increase Theory of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Although two studies in the current review reported that autistic children can be taught to engage in gameplay and pro-social verbal deception, it is unclear whether this represented improved ability and understanding as opposed to displaying learned behaviours associated with deception. However, the finding that ToM and executive function training increased ability on a gameplay deception task is consistent with other research showing that autistic children and adolescents who receive ToM or executive function training demonstrate improved social outcomes (Kenworthy et al, 2014; Lecheler et al, 2021 but also see Marraffa & Araba, 2016).…”
Section: Discussionsupporting
confidence: 89%
“…Although two studies in the current review reported that autistic children can be taught to engage in gameplay and pro-social verbal deception, it is unclear whether this represented improved ability and understanding as opposed to displaying learned behaviours associated with deception. However, the finding that ToM and executive function training increased ability on a gameplay deception task is consistent with other research showing that autistic children and adolescents who receive ToM or executive function training demonstrate improved social outcomes (Kenworthy et al, 2014; Lecheler et al, 2021 but also see Marraffa & Araba, 2016).…”
Section: Discussionsupporting
confidence: 89%
“…ToM deficits are common in youth with ASD (Lecheler et al , 2021) and are often linked to referential communication impairments (Sidera et al , 2018). ToM refers to the ability to make inferences or attributions about one’s own and others’ thoughts, feelings, perceptions and beliefs (Lecheler et al , 2021; Sevlever et al , 2013; Sidera et al , 2018).…”
Section: Vulnerability Of Autism Spectrum Disorder Youth To Child Mal...mentioning
confidence: 99%
“…ToM deficits are common in youth with ASD (Lecheler et al , 2021) and are often linked to referential communication impairments (Sidera et al , 2018). ToM refers to the ability to make inferences or attributions about one’s own and others’ thoughts, feelings, perceptions and beliefs (Lecheler et al , 2021; Sevlever et al , 2013; Sidera et al , 2018). Individuals with ASD who have ToM deficits can be at risk for CSA because of an inability to understand the motives, emotions or deceptions of CSA offenders (Lecheler et al , 2021).…”
Section: Vulnerability Of Autism Spectrum Disorder Youth To Child Mal...mentioning
confidence: 99%
“…Altered Theory of Mind has been suggested as an element in autism for many years (for example, Baron-Cohen, 1997;Charman and Baron-Cohen 1995;Karmiloff-Smith et al 1995;Frith 2003) and a difference in the development of ToM is considered a core challenge in autism (for example, Seidman andYirmiya 2018, in Whalon andCox 2020). Recent studies continue to explore ToM "impairment" in both children (for example, Lecheler et al 2020) and adults (for example, Rosenthal et al 2019), frequently positioning these studies within explorations of support for ToM (Holopainen et al 2019;Lecheler et al 2020) or exploring ToM as an element to examine or decode autism presentation (Livingston et al 2019). Reading is a complex task involving the application of knowledge of vocabulary and grammar, together with accessing of prior knowledge, the generation of inference, self-monitoring of understanding and the integration of each of these with information from the text (Kim 2017), with ToM increasingly recognised as an important element to the successful management of this task (Atkinson et al 2017;Dore et al 2018).…”
Section: Literaturementioning
confidence: 99%